2016
DOI: 10.29244/jipthp.4.3.386-389
|View full text |Cite
|
Sign up to set email alerts
|

Kualitas Fisik, Mikrobiologis, dan Organoleptik Daging Ayam Broiler pada Pasar Tradisional di Bogor

Abstract: In Indonesia, broiler meat is available abundant mainly in traditional market. Unfortunately, this kind of meat is perishable most physical, organoleptic, and microbiological deterioration. To conserve consumers from low quality of meat, this study was conducted to evaluate the physical, organoleptic, and microbiological quality of meat. Meat evaluated was obtained from three traditional markets determined purposively, namely A market, B market, and C market. The physical quality measured were pH and a w ; the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
14

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 5 publications
0
13
0
14
Order By: Relevance
“…It was lower than the report from Kholifah et al (2016) in Samarinda City, Indonesia, but higher than Naik et al (2015) in India and Alali et al (2012) in Russia. Hajrawati et al (2016) reported that the intrinsic parameters of chicken carcasses in the Indonesian market were 0.84-0.85 for water activity and 6.00-6.37 for pH. This condition is suitable for Salmonella spp.…”
Section: Resultsmentioning
confidence: 96%
“…It was lower than the report from Kholifah et al (2016) in Samarinda City, Indonesia, but higher than Naik et al (2015) in India and Alali et al (2012) in Russia. Hajrawati et al (2016) reported that the intrinsic parameters of chicken carcasses in the Indonesian market were 0.84-0.85 for water activity and 6.00-6.37 for pH. This condition is suitable for Salmonella spp.…”
Section: Resultsmentioning
confidence: 96%
“…Cinnamon, gotu kola and their combination had the same effect on the texture of pectoral meat in quail. Hajrawati et al (2016) stated that the texture of the meat is influenced by feed besides being also influenced by age, activity, and gender. This is indicated by the condition of meat that is almost the same in each treatment, which is chewy.…”
Section: Resultsmentioning
confidence: 99%
“…The difference in myoglobin is caused by the type of fiber in the muscle (Suman & Joseph, 2013;Yin et al, 2011;Genchev et al, 2008). Hajrawati et al (2016) stated that the color of poultry meat is influenced by several factors such as age, sex, taxon, cage environment, cutting environment, conditions before cutting, cutting and storage conditions, intramuscular fat, meat water content and feed. Qiao et al (2011) stated that the color of meat is influenced by the water content and pH of the meat.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nilai pH tersebut berada sedikit lebih tinggi dari penelitian Hajrawati et al (2016) Kondisi visual daging dipengaruhi oleh adanya white striping yang merepresentasikan kondisi kerusakan daging yang berdampak pada penentu preferensi konsumen terhadap daging ayam. Pada penelitian ini, dimensi lebar white striping signifikan lebih besar pada zona penempatan ayam lebih jauh dari inlet dan kandang lebih pendek namun signifikan lebih kecil pada penempatan ayam zona 4 dan kandang lebih panjang.…”
Section: Kualitas Fisik Dagingunclassified